2022
DOI: 10.1021/acs.est.2c02844
|View full text |Cite
|
Sign up to set email alerts
|

State-Space-Based Framework for Predicting Microbial Interaction Variability in Wastewater Treatment Plants

Abstract: Substantial attempts have been made to control microbial communities for environmental integrity, biosystem performance, and human health. However, it is difficult to manipulate microbial communities in practice due to the varying and nonlinear nature of interspecific interaction networks. Here, we develop a manifoldbased framework to investigate the patterns of microbial interaction variability in wastewater treatment plants using manifold geometric properties and design a simple control strategy to manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…We found that several core denitrifying bacteria lack key NO reduction genes, such as the strict core genus Desulfobacillus, revealing an overlooked synergy between anammox and denitrifying bacteria using NO as an intermediate. Additionally, our ndings revealed that the strong correlation between the genera Denitratisoma and anammox bacteria [23,76] was probably due to the key role of the phylogenetically similar genus Desulfobacillus in anammox microbiota. This interspecies interaction is more likely to depend on NO instead of nitrite, which warrants veri cation in future studies [86].…”
Section: Novel Insights Into the Functional Diversity Of Anammox Micr...mentioning
confidence: 84%
See 1 more Smart Citation
“…We found that several core denitrifying bacteria lack key NO reduction genes, such as the strict core genus Desulfobacillus, revealing an overlooked synergy between anammox and denitrifying bacteria using NO as an intermediate. Additionally, our ndings revealed that the strong correlation between the genera Denitratisoma and anammox bacteria [23,76] was probably due to the key role of the phylogenetically similar genus Desulfobacillus in anammox microbiota. This interspecies interaction is more likely to depend on NO instead of nitrite, which warrants veri cation in future studies [86].…”
Section: Novel Insights Into the Functional Diversity Of Anammox Micr...mentioning
confidence: 84%
“…Moreover, with the discovery of novel species, including anammox bacteria, the study of species diversity has become highly important in anammox systems [19,20]. However, a large proportion of microorganisms and their functional potential in anammox systems are overlooked [21][22][23], largely due to the low taxonomic resolution of genomes [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, multitype electron-capturing coupled NO 3 – -N reduction metabolic pathways were also identified in the PRO3 ( Denitratisoma ) genome, including the TCA cycle, rASR pathway, and denitrification-related gene clusters assigned to this bin. Generally, Denitratisoma is classified as a heterotrophic denitrifying organism . Under C-org feeding, Denitratisoma expressed respiratory nitrate reductase genes ( narGH / napAD ), which reduce NO 3 – -N to NO 2 – -N and require the transport of NO 3 – -N into the cell inner membrane and cytoplasm .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, Denitratisoma is classified as a heterotrophic denitrifying organism. 23 Under C-org feeding, Denitratisoma expressed respiratory nitrate reductase genes (narGH/napAD), which reduce NO 3 − -N to NO 2 − -N and require the transport of NO 3 − -N into the cell inner membrane and cytoplasm. 21 However, when pyrites were injected, PRO3 developed the rASR pathway (working principle refers to PRO2) in parallel to sharing the C-org metabolic load.…”
Section: Transformation In Nutritional Behaviors Ofmentioning
confidence: 99%